2019
DOI: 10.2139/ssrn.3308537
|View full text |Cite
|
Sign up to set email alerts
|

Financial Literacy and Fraud Detection

Abstract: Who is better at detecting fraud? This paper finds that more financially knowledgeable individuals have a higher propensity to detect fraud: a one standard deviation increase in financial knowledge increases fraud detection probabilities by 3 percentage points. The result is not driven by individuals' higher financial product usage and is observed to be moderated by individuals' low subjective well-being, effectively depleting skills to detect fraud. Interestingly, prudent financial behavior relating to basic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…The results of this study show that parents' education has positive impacts on financial socialization, financial literacy and financial well-being. The results confirm the assertion that parents' education influences the quality of parental financial socialization (Engels et al , 2020) and indicate that parents' education is an important factor that cannot be ignored in future family financial socialization research. Parents are encouraged to obtain higher education to benefit their children.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of this study show that parents' education has positive impacts on financial socialization, financial literacy and financial well-being. The results confirm the assertion that parents' education influences the quality of parental financial socialization (Engels et al , 2020) and indicate that parents' education is an important factor that cannot be ignored in future family financial socialization research. Parents are encouraged to obtain higher education to benefit their children.…”
Section: Discussionsupporting
confidence: 82%
“…Sherraden (2013) noted that if parents lack financial knowledge or experience, they not only cannot effectively teach or model behaviors for their children, but may also even teach or model detrimental financial behaviors. In addition, previous researchers believed that parents' education may have a strong correlation with their financial knowledge and can influence the quality of parental financial socialization (Engels et al , 2020). Thus, parents' education was included as a control variable in this study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The 2011 FTC survey reported that consumers with less numeracy skills are more likely to be victimized by fraud [46]. An earlier study suggests that financial knowledge rather than basic money management skills are necessary to navigate increasingly sophisticated fraud and scam schemes [47]. A previous review reported that the literacy and fraud relationship depends on the types of fraud, where victims of investment fraud tend to be more financially literate, while lottery fraud victims on the other hand are less literate [48].…”
Section: Discussionmentioning
confidence: 99%
“…For young adults, the notion of increased complexity of financial products and increased choice is relevant as, after graduating from secondary school, students and young adults face increasingly complex and important financial decisions in the pursuit of financial well-being while balancing the temptations of a consumption-based global economy (Sundarasen, 2017). Engels et al (2020) found that, those with more financial expertise are better at detecting fraud. Further, Joo and Grable (2004) revealed a mediating effect of financial knowledge on financial well-being.…”
Section: Literature Review Financial Knowledgementioning
confidence: 99%